Bodies of Fashion and the Fashioning of Subjectivity. (December 2020) - Eckersley, Andrea; Duff, Cameron
This article explores the links between habit, fashion and subjectification to extend analysis of the clothed body beyond the semiotic frames that have tended to dominate discussions of fashion across the social sciences and humanities. Our goal is to explain how fashion's diverse materialities participate in the modulations of subjectivity, affecting bodies in diverse encounters between matter, signs and practices. We develop our analysis by way of Gilles Deleuze's discussion of encounters, habit and memory. Our principal contention is that fashion may usefully be theorised in terms of specific habits of coordination by which affects, memories, sensations and desires are transmitted between bodies in varied spatial, temporal, material and affective encounters. Following the work of John Protevi, we argue that such coordination expresses a distinctive mode of subjectification according to the specific encounters immanent to it. We ground this discussion in detailed analysis of the work of Melbourne artist Fiona Abicare. Abicare's installation and performance-based practice invokes the affective and habitual aspects of fashion as each is instantiated in encounters between bodies. Abicare's attention to the habits and memories of the clothed body alludes to the varied practices of subjectification by which diverse subjects of fashion emerge.